2020
DOI: 10.1109/twc.2019.2951416
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Performance Analysis of Underwater Optical Wireless Relaying and Routing Techniques Under Location Uncertainty

Abstract: On the contrary of low speed and high delay acoustic systems, underwater optical wireless communication (UOWC) can deliver a high speed and low latency service at the expense of short communication ranges. Therefore, multihop communication is of utmost importance to improve degree of connectivity and overall performance of underwater optical wireless networks (UOWNs). In this regard, this paper investigates relaying and routing techniques and provides their end-to-end (E2E) performance analysis under the locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…In UOWC, the optical signal received at each hop is converted into an electrical signal, which is then decoded, encoded, and transmitted to the next hop in DF transmission [185]. Although DF greatly improves electrical-to-electrical performance by limiting background noise propagation, it introduces additional power consumption and signal processing delays.…”
Section: ) Different Protocols In Uowcmentioning
confidence: 99%
See 1 more Smart Citation
“…In UOWC, the optical signal received at each hop is converted into an electrical signal, which is then decoded, encoded, and transmitted to the next hop in DF transmission [185]. Although DF greatly improves electrical-to-electrical performance by limiting background noise propagation, it introduces additional power consumption and signal processing delays.…”
Section: ) Different Protocols In Uowcmentioning
confidence: 99%
“…For latter, after it received the light signal, and then converted it to electrical signal, next to decoded, eventually re-encoded and forward to the next hop. Thus, DF relaying needs converter, decoder, and encoder with high-speed data to achieve data rates for Gbps [185].…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%
“…Whereas the latter is due to photons propagating direction, which is changing randomly because of (i) interaction with the water particles with sizes comparable to the carrier wavelength (i.e., diffraction); and/or (ii) changing refractive indices (i.e., refraction). In turbid waters, especially coastal and harbor, the transmitted photons will experience multiple scattering [11,12]. In [13], it is shown that the multiple scattering and system geometries affected the temporal dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…ERA-based protocols are of great importance, as energy is conscious or residual energy is increasing uniformly across the network, and find the right pathways and long network lives. 27…”
Section: Introductionmentioning
confidence: 99%